Molecular genetic characteristics of X-linked retinoschisis in Koreans - Kim, So Yeon (Molecular Vision, 2009)
PURPOSE: X-linked retinoschisis (XLRS) is a recessively inherited disorder that causes macular degeneration and resultant visual defect in young males. Many genetic studies had focused on the patients in Western countries. We characterized the mutational spectrum of the RS1 gene in Korean patients with XLRS, and aimed to provide genetic information of XLRS in an Asian population. METHODS: This study enrolled 17 unrelated probands and their mothers for molecular genetic evaluation. All exons and the flanking intronic regions of RS1 were analyzed by direct sequencing. We performed gene dosage analysis by semiquantitative multiplex PCR to rule out the possibility of duplication in a patient without a sequence variation. We also tried RT–PCR analysis in a case with a putative splicing mutation. RESULTS: Genetic tests revealed 16 Korean patients (94.1%) had RS1 mutations. In one patient, neither sequence variation nor deletion or duplication in RS1 was detected. One case with de novo mutation was confirmed by familial analysis. Identified were 14 causative mutations, three of which were novel: one missense mutation (c.227T>G, p.V76G) and two splice-site mutations (c.78+1G>T and c.78+5G>A). No obvious genotype-phenotype relationship was observed. CONCLUSIONS: A missense mutation was the predominant type, and common or founder mutations were not observed in the Korean patients in this study who had XLRS. This study provides molecular genetic characteristics about an Asian population previously unexplored. The genetic characteristics of Korean XLRS will be helpful for understanding the worldwide spectrum of RS1 mutation.